PENGARUH GAYA HIDUP, CITA RASA DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN ULANG (Studi Pada Konsumen Kopi Sabin Banjarnegara) - Mega, Yuni; Maesaroh, Siti; Suryani, Ratna (Medikonis, 2024)
ABSTRACT The problem in this study is that there are consumers who are not satisfied with the lifestyle, taste, and brand image provided by Kopi Sabin. The aim of this research is to determine the influence of lifestyle, taste and brand image on repurchase decisions among Kopi Sabin Banjarnegara consumers. This type of research is quantitative research. Data collection was carried out using a questionnaire, data obtained from a sample of the research population, namely 87 consumers. The sampling technique in this research used a purposive sampling method. Data analysis uses multiple linear regression. Quantitative analysis in research uses validity and reliability tests with Cronbach's Alpha. The classical assumption test includes normality test, heteroscedacity test and multicollinearity test. The results showed that partially lifestyle affects repurchase decisions, taste affects repurchase decisions while brand image has no significant effect on repurchase decisions. Simultaneously, lifestyle, taste and brand image have a significant influence on repurchase decisions, as evidenced by the coefficient of determination of 57.8%, the remaining 42.2% is influenced by other variables not included in this research. Suggestions for future researchers are that researchers should be able to develop research with other variables.